The determinants of BUND-future price changes: An ordered probit analysis using DTB and LIFFE data - Ulrich Kaiser (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1997)
This paper investigates the determinants of transaction price changes during BUND-future trading at Deutsche Terminbörse (DTB) and London International Financial Futures Exchange (LIFFE). The analysis uses the ordered probit model, which is an econometric tool that is comparatively new to the econometrics of financial markets. It is especially valuable with respect to high frequency data which are used for the empirical analysis of this paper. Although the ordered probit model is nonstructural, it allows to test the validity of market microstructure literature. A comparison of BUND-futures trading at DTB and LIFFE is also conducted. ; In dieser Arbeit werden die Determinanten von Transaktionspreisveränderungen während des BUND-Future Handels an der Deutschen Terminbörse (DTB) und der London International Financial Futures Exchange (LIFFE) untersucht. Die Analyse wird mit Hilfe eines geordneten Probitmodells durchgeführt, das bisher kaum für Finanzmarktdaten verwendet wurde. Obwohl das geordnete Probitmodell nichtstrukturell ist, erlaubt es, einige mikroökonomische Ansätze zur Erklärung bestimmter Marktphänomena auf ihre Richtigkeit hin zu Überprüfen. Die Untersuchung verwendet dabei Hochfrequenzdaten, deren Eigenschaften das geordnete Probitmodell in besonderem Maße Rechnung trägt. Außerdem wird ein Vergleich zwischen den beiden Börsen DTB und LIFFE angestellt.
Keywords: 330